Poéticas da tradução e identidades: Paulo Henriques Britto tradutor de Elizabeth Bishop - OLIVEIRA, Fátima Cristina Rivas Filipe de (2016)
The aim of this research is to investigate issues related to the "task of the translator" (an expression created by Walter Benjamin), emphasizing the poetic of translation of the Brazilian contemporary poet, Paulo Henriques Britto, and his recreations and translations of the North American modernist poet Elizabeth Bishop, besides the creative capacity required from the translators of lyric, highlighting the strong signs of their identities in their work, having as support the book Poemas Escolhidos of Elizabeth Bishop (2012), organized by his selection of poems, introductory texts and translations. The poetics of translation is analyzed from the point of view of Paulo Henriques Britto nowadays, as well as the issues related to the interference of the identity and globalization in the way the current translation is being faced. We conducted a survey of the historical and technical aspects of translation, taking into account the stylistic factors involved. The mention of the term poiesis intends to alert to the fact that, in the case of the "poetic translation" or "transcreation" - referring to the Brazilian poet Haroldo de Campos as a translator - the technical knowledge is important as well as a kind of "ownership" by the translator of the original work. Aspects related to the theory and the "translation practice" will be studied by means of interdisciplinary elements that approximate the previous studies made on the Histories of Translation and Literature. Some political and cultural issues in the history of the modern and contemporary translation will be mentioned, through examples of the theories created at these moments and inserted in the technical aspects of translation. Basically, the studies about poietic translation and the poetic of translation of Paulo Henriques Britto will be focused, presenting the excellence of this translator through his deep knowledge of the life and work of Elizabeth Bishop.